CHAOS ENGINEERING: STRESS-TESTING MICROSERVICES FOR RESILIENCE - Venkata Durga Ganesh Nandigam, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
In the realm of distributed systems, microservices architectures have become the cornerstone for building scalable and flexible applications. However, with the increased complexity and interdependence of services, ensuring system resilience against failures has become a significant challenge. Chaos Engineering emerges as a proactive approach to enhance the robustness of microservices by intentionally introducing failures and observing system behavior under stress. This article explores the principles and practices of Chaos Engineering as a method for stress-testing microservices to achieve resilience. It examines the inherent complexities of microservices architectures, including service dependencies, network uncertainties, and emergent behaviors that traditional testing methods may not uncover. Through real-world case studies and implementation strategies, it demonstrates how organizations have successfully adopted Chaos Engineering to identify vulnerabilities, improve system reliability, and build resilient architectures. The article also discusses emerging trends, including AI-driven experimentation, security chaos engineering, and applications in edge computing environments, highlighting the evolution and future directions of this critical discipline.